Arabic Language Curriculum in Southeast Asia: A Comparative Analysis of Indonesia and the Philippines - Rivera, John Robert; Hikmah Maulani; Mohamad Zaka Al Farisi (IAIN Madura, 2025)
This study aims to compare the design, implementation, and evaluation of Arabic language curricula in Indonesia and the Philippines, as two national Arabic language curriculum systems in the Southeast Asian region. Employing a qualitative approach with a comparative case study design, the study utilizes document analysis as its primary method. Core data sources include Indonesia’s 2013 Curriculum and Merdeka Curriculum, as well as the Arabic Language and Islamic Values Education (ALIVE) program in the Philippines. The analysis applies Posner’s five dimensions of curriculum; purposes, content, organization, implementation, and evaluation. The findings indicate that Indonesia’s curricula are centered on classical textual literacy and grammatical precision, yet lack adequate attention to oral communication skills. In contrast, the ALIVE curriculum promotes functional speaking ability from early stages but is limited in linguistic depth and assessment standardization. Both approaches demonstrate strengths and limitations in fostering comprehensive Arabic language competence. The study recommends the development of a more balanced curriculum integrating classical literacy and oral proficiency, supported by targeted teacher training and context-sensitive evaluation frameworks.